Communication and touristic image, synergy for rural community destinations development - Herrera Rivas, Keila Ketty; Vilema Herrera, Keila Estefania (Scripta Mundi, 2022)
This research about rural community destinations is descriptive and, with a qualitative focus, based on the bibliographic review, adoptsthe communication and touristic image as study variables, with the aim of achieving a conceptualization of both terms, in order to understand their interrelation in the tourism, in view of its involvement in the cultural exchange and influence on tourists and the recipient community, for the internal and external promotion of the touristic destination through the analysis of diffusion models and the creation of the perceived and projected local image, with the adoption of digital resources with audiovisual content for the target public, the new generations, the new consumers.
Keywords: Touristic image; communication; audiovisual communication; tourism; consumers